Percepção de mães sobre vínculo e separação de seus bebês em uma unidade prisional feminina na cidade de São Paulo-SP - Torquato, Aneliza de Lima [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Brazilian female prision population increasead by almost 100% in six years. However, it was noted that is a lack of research regarding to imprisonment of women, especially those which are with their babies in prison. The law 11.942/2009, article 89 ensures the mother to stay with your child for at least six months, depending on the structural conditions of imprisonment. Thus, the stay of babies with their mothers in prison is temporary. This research goal was to understand the process of establishing of mother-infant link and the process of separation from the maternal point of view, under a women's prison unit. Five mothers participated of this research. They were between 21 and 34 years old and are arrested for the firs time. To collect data for the research, was utilized a form of socio-demographic data and was applied and individualized semi-structured interview which was recorded and full transcribed in order to evaluate two moments: first, when the mothers were with their babies in prison, and second, when only one mother o the groupo remained in the prison after the serparation of her child. The contents of the interviews passed through discourse analysis. It was found that the experience of motherhood in prison is permeated by feelings of loss, fears, guilt, loneliness, insecurity and suffering due to the possibility of separation of the child. It was shown that in this period, approximately six months of living with their babies, the relationship becomes too intense, since the routine is pretty much the same, where the greatest obligation is to care of the child. The participants were very caring and loving with the children able to pursue motherhood. However, all of them expressed feeling of guilt for keeping their children in that environment and the negligence of institution with their babies, in relation to medical care, food and access to material resources for child care. The study points to the needs for greater physical...

A população prisional feminina brasileira aumentou em quase 100% em seis anos. No entanto, nota-se carência de pesquisas que abordem o encarceramento de mulheres, principalmente das que estão com seus bebês na prisão. A Lei 11.942/2009, em seu artigo 89, garante à mãe ficar com seu filho durante no mínimo seis meses, dependendo das condições estruturais da prisão. Assim, a permanência dos bebês com suas mães na prisão é temporária. Esta pesquisa teve como objetivo compreender o processo de estabelecimento do vínculo mãe-bebê e o processo de separação, do ponto de vista materno, no âmbito de uma unidade prisional feminina. Participaram cinco mães, com idade entre 21 e 34 anos que estavam presas pela primeira vez. Para a coleta de dados utilizou-se de uma Ficha de dado sócio demográfico e de uma entrevista semiestruturada, realizada individualmente, gravada e transcrita na íntegra, para avaliar dois momentos: o primeiro, quando as mães estavam com seus bebês na prisão e, o segundo, quando apenas uma mãe do grupo permaneceu na prisão após vivenciar a separação do filho. Os conteúdos das entrevistas passaram pela análise de discurso. Foi possível constatar que a vivência da maternidade no cárcerer é permeada por sentimentos de perdas, medos, culpa, solidão, insegurança e sofrimento em virtude de possibilidade de separação do filho. Comprovou-se que nesse período, de aproximadamente seis meses de convivência com os bebês, a relação se torna muito intensa, já que a rotina é praticamente a mesma, onde a maior obrigação é o cuidado com a criança. As participantes se mostraram muito cuidadosas e amorosas com os filhos, capazes de exercer a maternidade. Todavia, todas as manifestações sentimento de culpa por manter os filhos naquele ambiente e o descaso da instituição para com seus bebês, tanto em relação a atendimento médico quanto a alimentação e acesso a meios materiais para o cuidado...
Keywords: Maternidade; Prisão; Mãe e filhos; Motherhood